(untitled) (Journal of Geography and Environmental Management, 2018)
The conditions of modernity require a new direction in the development of world tourism, aimed at finding non-traditional approaches to rethinking human well-being, and deepening cooperation for the achievement of human security in the context of sustainable development. Therefore, the problems of greening the spheres of human activity, including tourism, are the most urgent for today. Ecologization, being an important part of the “green” economy, is aimed at maintaining the well-being of society through the rational use of natural resources, as well as the return of end products to the production cycle (Pásková, 2012: 113; TravelifeSustanability System Criterie, 2012). In the article approaches of ecologization of tourist activity on the basis of program provisions of “green” economy are considered, principles of ecologization of tourism are revealed, and also positive and negative influence of tourism on environment is analyzed. At the same time, the experience of the ecologization of tourist activity in foreign countries has been studied and ways of ecologizing tourism based on the use of modern technologies, efficient energy use, the introduction of closed technological cycles are proposed.